Reduction of Particulate Matter Emissions in EU Inland Waterway Transport - Spoof-Tuomi, Kirsi (My University, 2016)
In September 2014, the European Commission adopted a proposal on new requirements relating to emission limits and type-approval for non-road engines. The introduction of a new emission stage (Stage V) establishes extremely tight limits for particulate matter emissions for mobile non-road applications, including inland waterway vessels. These new emission limits will eventually require many ships to apply efficient exhaust gas after-treatment technology. The aim of this study was to find out which kinds of exhaust gas after-treatment solutions could fulfil these tightening particulate emission standards in EU inland navigation. A marine dual fuel engine was used as an example. The engine can be run both with gas and diesel fuel. The first part of the study consists of a literature review of various exhaust gas after-treatment technologies. This part serves as a general technology guide for particulate emission abatement from diesel engines. In the second part of the study, different supplier technologies and solutions were evaluated. The targets for particulate filtering system were defined and a specific inquiry was sent to potential suppliers. Based on the replies, passive diesel particulate filter systems with catalytic coating or/and an upstream diesel oxidation catalyst can be regarded as the primary choice for particulate emission control in inland navigation. This study was conducted as part of the EU Hercules-2 research and development programme, aimed at fostering environmentally sustainable and more efficient shipping.
Keywords: inland waterway transport; gas and diesel engines; particulate matter emissions; diesel particulate filter; fi=Energiatekniikka|en=Energy Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|